Determine flood extent using hecras / Shahirah Ngah - Ngah, Shahirah (2019)
Flood in Perlis is common issue because Perlis is among the state in Malaysia that received heavy rain throughout the year. However, the most serious flood disaster happen in Perlis are in year 2005, 2010, and 2011. Statistic flood disaster from November 2010 to April in Perlis show total victims are 15 261 and 2921 families and Kangar is the worst affected area of the flood. An exceptional rainfall at that time had caused water levels in the rivers, and water from Timah Tasoh Dam has overflowed. This is the major factor that led to flooding. The coordinate for this study area Tebing Tinggi, Perlis is 6° 26' 0" N, 100° 10' 0" E. In this study, it is aimed to determine the flood extent using HecRAS includes three main objectives; to delineate flood extent using existing Sungai Perlis, to verify processed flood extent using HecRAS with satellite derived water index and to identify the affected area of Timah Tasoh west flood diversion on flood plain. The methodology is applied to know flood extent based on software HecRAS. The result of the research indicate that HecRAS and GIS is an effective tool for flood extent mapping and analysis.